Scaffolding in Supporting Senior High School Students’ Critical Thinking Skills in Sequences and Series Problems - Savirra Tazkia; Tatag Yuli Eko Siswono (Program Studi S1 Matematika UNESA, 2023)
Critical thinking skills are important for every individual, that they need to be developed in classroom learning, one of which is through learning sequences and series material. However, there are still many students who have difficulty solving problems on sequences and series material, so they need help using scaffolding. This study aims to describe students' thinking skills on sequences and series material, as well as scaffolding which helps students' critical thinking skills in solving sequence and series material questions. The subjects of this study were 2 students who failed to complete the two critical thinking skills tests given. The two students were then interviewed and given scaffolding. The interviews were conducted in a semi-structured manner, that the researcher prepared several questions which could indicate indicators of critical thinking skills, as well as scaffolding which could assist students in solving problems, but the researcher was free to improvise by asking for other information according to the conditions during the interview. The data obtained was then analyzed by reducing the data, presenting the data, and drawing conclusions. The results showed that scaffolding in the form of reviewing played a dominant role for supporting the failure of critical thinking skills on the indicators of interpretation, analysis, evaluation and explanation. Restructuring helps the failure of critical thinking skills on the indicators of interpretation. Explaining helps the failure of critical thinking skills on evaluation indicators. Developing conceptual thinking helps indicators of critical thinking skills analysis, inference, and self-regulation.